2004
DOI: 10.1097/01.ju.0000140501.68841.a1
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Enucleation Versus Transurethral Resection of the Prostate: Results From a 2-Center, Prospective, Randomized Trial in Patients With Obstructive Benign Prostatic Hyperplasia

Abstract: HoLEP and TURP were equally effective for relieving obstruction and lower urinary tract symptoms. HoLEP was associated with shorter catheterization time and hospital stay. At 1 year of followup complications were similar in the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(121 citation statements)
references
References 15 publications
9
104
1
1
Order By: Relevance
“…18 In present study, no urinary incontinence secondary to sphincteric injury was observed. Three patients had transient urge incontinence.…”
Section: Discussionsupporting
confidence: 38%
“…18 In present study, no urinary incontinence secondary to sphincteric injury was observed. Three patients had transient urge incontinence.…”
Section: Discussionsupporting
confidence: 38%
“…Outcomes studies have documented substantial and durable improvement in symptom scores, QoL scores, and urodynamic parameters. Moreover, at 6 to 48 months of follow-up, HoLEP has been shown to provide symptomatic and urodynamic improvements similar to TURP [28,29,[48][49][50][51]. Additionally, HoLEP is proven to be effective for patients with even the largest prostates.…”
Section: Holmium Laser Enucleationmentioning
confidence: 87%
“…Other complications associated with HoLEP, including sexual dysfunction, dysuria, AUR, urinary incontinence, urethral stricture, bladder neck contracture, and urinary tract infections, are either equivalent or improved when compared with TURP [28,29,50,51]. Bladder mucosal injury during the tissue morcellation process required to remove large prostate tissue volumes occurred in 18% of cases in a study by Montorsi et al [51].…”
Section: Holmium Laser Enucleationmentioning
confidence: 94%
“…In randomized controlled trials comparing Holmium laser enucleation versus TURP, with more than 350 patients, both procedures were highly effective in terms of urodynamic findings and subjective symptom scoring. HoLEP was significantly superior to TURP in terms of catheter time, hospital stay and hemoglobin loss, but operative time was longer [26][27][28].…”
Section: Laser Prostatectomymentioning
confidence: 92%